Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm given $a_1, a_2, a_3$ as roots of the equation $x^3 + 7x^2 - 8x + 3$ and need to find the cubic polynomials with roots $a_1^2, a_2^2, a_3^3$ and $\frac{1}{a_1}, \frac{1}{a_2}, \frac{1}{a_3}$. It's in a chapter about Galois Theory and is preceded by a problem about elementary symmetric polynomials. I'm guessing I need to use elementary symmetric polynomials to solve for the two desired functions, but I really don't know where to start. Hints would be much appreciated.

share|improve this question

3 Answers 3

$a$, $b$ and $c$ are the roots of $x^3 + px^2 + qx + r$ if and only if $abc = -r$, $ab+bc+ca=q$ and $-(a+b+c)=p$.

We have $\frac{1}{a_1} \cdot \frac{1}{a_2} \cdot\frac{1}{a_3} = \frac{1}{a_1a_2a_3} = -1/3$, $\frac{1}{a_1} + \frac{1}{a_2} + \frac{1}{a_3} = \frac{a_1a_2 + a_2a_3 + a_3a_1}{a_1a_2a_3} = \frac{-8}{-3}$ and $\frac{1}{a_1a_2} + \frac{1}{a_2a_3} + \frac{1}{a_3a_1} = \frac{a_1+a_2+a_3}{a_1a_2a_3} = \frac{-7}{-3}$. It follows that $\frac{1}{a_1} $, $\frac{1}{a_2} $ and $\frac{1}{a_3} $ are the roots of $X^3 - \frac{8X^2}{3} + \frac{7X}{3} + \frac{1}{3}$. The problem with $a_1^2$, $a_2^2$, $a_3^2$ can be solved similarly.

share|improve this answer
    
Alright, I've followed that part of the question with the inverse roots. For finding the roots' squares, I have $-3 = a_1\cdot a_2\cdot a_3 \Rightarrow a_1^2\cdot a_2^2\cdot a_3^2 = 9$ which is straightforward. I also have $a_1^2 + a_2^2 + a_3^2 = 65$. Right now I'm stuck trying to simplify $a_1^2a_2^2 + a_1^2a_3^2 + a_2^2a_3^2$. –  user2049004 Mar 11 at 23:56
    
Use $(ab)^2 + (bc)^2 + (ca)^2 = (ab+bc+ca)^2 - 2abc(a+b+c)$. –  user133281 Mar 12 at 6:39

Extended hints (for a trick that avoids using the elementary symmetric polynomials in the case of squares):

For any polynomial $p(x)$ we can write the product $p(x)p(-x)$ as polynomial $f(x^2)$ because $p(x)p(-x)$ is even. Furthermore $\deg f=\deg p$. If $\alpha$ is any zero of $p(x)$ show that $\alpha^2$ is a zero of $f(x)$. Here (you do this calculation, too) $$p(x)p(-x)=9 - 22 x^2 + 65 x^4 - x^6,$$ so we get $f(x)=9-22x+65x^2-x^3.$ Why does this solve your question?

share|improve this answer

Here is another method, which avoids symmetric polynomials - though in the context you might be expected to use them. If fact you can use this method, if you track coefficients, to work out how the symmetric polynomials combine.

For the squares of the roots you need to find a polynomial satisfied by $y=x^2$ and you have $$0=x^3+7x^2-8x+3=x(y-8)+7y+3$$

Whence $$x(8-y)=7y+3$$ Square both sides $$x^2(8-y)^2=(7y+3)^2 \text { or }y(8-y)^2=(7y+3)^2$$

The last equation gives you a cubic in $y$ when you simplify it.


For the second case put $y=\frac 1x$ whence $x=\frac 1y$

$$\frac 1{y^3}+7\frac 1{y^2}-8\frac 1y+3=0$$

Multiply through by $y^3$ to get a cubic in $y$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.